The Effect of Gas Flow Rate, Solid-To-Solvent Ratio, and Temperature on Micro-Carbon Synthesis from Pine Resin using Spray Pyrolysis and The Application as Masks Coating Material - Jayadi Jayadi; Wahyu B. Widayatno; Agus S. Wismogroho; Marga A. J. Mulya; Akhiruddin Maddu; Yessie W. Sari (International Journal of Technology)
This study aims to develop an additional layer in masks using micro-carbon to enhance protection against inhalation of droplets. Carbon microstructures were obtained using spray pyrolysis method, with the precursor being resina colophonium dissolved in acetone and ethyl acetate. Subsequently, the effect of varying the precursor-solvent ratio, heating temperature, and nitrogen flow rate on the shape, size, and content of the products was assessed. The results showed that the highest carbon content achieved was approximately 96%, with the smallest size measuring 139 nm. The penetration test results after applying the product on masks fabric revealed a significant reduction in penetration up to level 2. In addition, the contact angle test showed that the addition of carbon led to a lower reduction (6.7°) compared to regular masks fabric with a 20.4° decrease. This improvement could contribute to reducing the risk of droplet inhalation during masks application.